Ipnv Modulation of Pro and Anti-Inflammatory Cytokine Expression in Atlantic Salmon Might Help the Establishment of Infection and Persistence - Sandino-Garcia, A; Imarai-Bahamonde, C; Maisey-Munoz, K; Reyes-Cerpa, S; Toro-Ascuy, D; Ibanez-Vega, J (2012)
IPNV is the agent of a well-characterized acute disease that produces a systemic infection and high mortality in farmed fish species and persistent infection in surviving fish after outbreaks. Because modulation of the host expression of pro and anti-inflammatory cytokines can help establish persistence, in this study, we examined the expression of IL-1?, IL-8, IFN?1 and IL-10 during acute and persistent IPNV infection of Atlantic salmon. Results showed that IPNV infection induces an increase of the IFN?1 and IL-10 mRNA levels in the spleen and head kidney (HK) of fish after acute experimental infection. Levels of the pro-inflammatory cytokines IL-1? and IL-8 did not rise in the spleen although an increase of IL-1?, but not of IL-8, was observed in head kidney. In carrier asymptomatic salmon, cytokine gene expression of IFN?1 in the spleen and IL-10 in head kidney were also significantly higher than expression in non-carrier fish. Interestingly, a decrease of IL-8 expression was also observed. IPNV infection of SHK-1, which is a macrophage-like cell line of salmon, also induced an increase of expression of the anti-inflammatory cytokine IL-10 with no effects on the expression of IL-1? and IL-8. The effects are induced by an unknown mechanism during viral infection because poly I:C and the viral genomic dsRNA showed the opposite effects on cytokine expression in SHK-1 cells. In summary, IPNV always induces up-regulation of the anti-inflammatory cytokine IL-10 in Atlantic salmon. As this is accompanied by a lack of induction of the pro-inflammatory cytokines IL-1? and IL-8, the anti-inflammatory milieu may explain the high frequency, prevalence and persistence of IPNV in salmon. Effects might be part of the viral mechanisms of immune evasion. © 2011 Elsevier Ltd.